Skrining Talasemia Minor Pada Pendonor di Unit Donor Darah Palang Merah Indonesia Kabupaten Majalengka - Winengsih, Wiwin; Novilla, Arina; Ningrum, Nining Ratna; Khairinisa, Gina (Anakes : Jurnal Ilmiah Analis Kesehatan, 2024)
Thalassemia is a hereditary hemolytic disease caused by a disorder in the synthesis of hemoglobin within red blood cells. Thalassemia prevention programs are beneficial for reducing or breaking the chain of thalassemia by preventing marriages between thalassemia carriers, which could result in thalassemia sufferers. One preventive measure is thalassemia screening. This study aims to identify the presence of thalassemia minor carriers among donors at the Indonesian Red Cross Blood Donation Unit in Majalengka Regency. The study is a descriptive quantitative research with a sample size of 92 donors who visited the Indonesian Red Cross Blood Donation Unit in Majalengka Regency. The thalassemia screening included hemoglobin tests, osmotic fragility tests, and erythrocyte indices. The results showed that all 92 donors had normal hemoglobin levels with an osmotic fragility test showing negative results using OTOF method. Therefore, further examination of the erythrocyte index was not conducted.. Based on these results, it can be concluded that there were no thalassemia minor carriers among the donors at the Indonesian Red Cross Blood Donation Unit in Majalengka Regency. Keywords  :Thalassemia, Donor,Osmotic Fragility, Hemoglobin